رسالة في بيع الوقف للشيخ نور الدين علي بن ياسين الطرابلسي المتوفي سنة "942 هـ." - الطرابلسي، نور الدين علي بن ياسين، ت. 942 هـ.; الجبوري، منال خليل سلمان (جامعة بابل - كلية التربية للعلوم الإنسانية, 2021)
يتلخص هذا البحث بسؤال سُئل به الشيخ نور الدين الطرابلسي عن بيع الوقف إن كان باطلاً أو فاسداً، وقد أجاب الشيخ بما زبدته أنه فاسد. وقد بدأ في وصوله لهذه النتيجة بالتعريف عن مصطلح (الباطل) و(الفاسد) عند أصحاب المذهب الحنفي، مع ضرب مثال لكل منهما، ثم تفريع كل واحد منهما على حدى، مبيناً أن هذه التعاريف مأخوذة من الكتب المعتمدة عند الحنفية كـ "الكنز" وشروحه و"الهداية" وشروحها وغير ذلك، ذاكراً حقوق كل العباد، ومبيناً تقديم حق العبد على حق الرب إذا اجتمعا (يَا أَيُّهَا النَّاسُ أَنتُمُ الْفُقَرَاء إِلَى اللَّهِ وَاللَّهُ هُوَ الْغَنِيُّ الْحَمِيدُ) ]فاطر: 15]، بأسلوب سهل، وذهن سيال. تم بين رحمه الله أخيراً أن جميع ما ذكره وقره منقول من كتب أئمة الحنفية، ومن نازع في شيء مما ذكره وقره، فهو بعيد عن العلم عنده.
This research is summarized by a question that Sheikh Nur al-Din al-Trabelsi was asked about selling the endowment if it was invalid or corrupt. He began to arrive at this conclusion by introducing the term “falsehood” and “corrupt” among the followers of the Hanafi school of thought, giving an example for each of them, then branching out each of them separately, indicating that these definitions are taken from the books adopted by the Hanafi school such as “Al Kanz” and its explanations. And “guidance” and its explanations and so on, mentioning the rights of all worshipers, and indicating the supremacy of the right of the servant over the right of the Lord if they meet [Fatir: 15], in an easy way, and with a flowing mind. Then, may God have mercy on him, finally, he explained that all that he mentioned and read was transmitted from the books of the Hanafi imams, and whoever disputes something about what he mentioned and reads, he is far from his knowledge. God only knows.
Keywords: الشريعة الإسلامية -- المذاهب الإسلامية -- احكام الأوقاف